PENGARUHi i DIVIDENi, LABA, DAN ARUS KAS OPERASI TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIAi - Sitompul, Sulastri; Janrosl, Viola Syukrina E (SCIENTIA JOURNAL, 2019)
Financial statement is onei of the main sourcess of statement information that is very important to custumer in economy decision making. Financial statement can be used by inventors to predict stock securities. Account securities are really influenced by the number of return that willy be obtainedg by company in the fture. The main requirement that is needed by investors to be willing to share the fund is trought capital market where it can comfort them to invest. The aim of this research is to know the influence of profit dividend and operation cash flow simultaneously and partially over stock return to manufacturing factory on food and beverage sektor that is listed in Indonesia Stock Excange where the method used to i chose the sample i is purposive sampling. The used method in this research is double linear regression esearch comer from Indonesia Stock Ex change by using documentatiion and referenc methode.